The disaster recovery handbook a step-by-step plan to ensure business continuity and protect vital operations, facilities, and assets - Wallace, Michael 1960- (American Management Association, 2011)
Katrina, 9/11, and the BP oil spill are the kinds of deep-impact disasters that every company dreads. But even everyday threats--a roof collapsing, a computer network failing, a gas truck toppling over on the highway and shutting down distribution lines--can seriously disrupt operations, sometimes permanently.
Includes bibliographical references and index. - Print version record
Keywords: Emergency management -- Handbooks, manuals, etc; Crisis management -- Handbooks, manuals, etc; Computer security -- Handbooks, manuals, etc; Data protection -- Handbooks, manuals, etc; Data recovery (Computer science) -- Handbooks, manuals, etc -- Planning; Business planning -- Handbooks, manuals, etc; Gestion de crise; Guides, manuels, etc; Sécurité informatique; Guides, manuels, etc; Protection de l'information (Informatique); Guides, manuels, etc; Récupération des données (Informatique); Planification; Guides, manuels, etc; BUSINESS & ECONOMICS; Strategic Planning; Business planning; Computer security; Crisis management; Data protection; Emergency management; Handbooks and manuals